ANALYSIS OF FACTORS AFFECTING AUDIT QUALITY (EMPIRICAL STUDY OF INDONESIAN MANUFACTURING COMPANIES IN THE TRANSPORTATION AND LOGISTICS SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE IN 2019 - 2021) - Dallih Hartanti; O. Feriyanto (Jurnal Scientia, 2023)
This study aims to analyze the factors that influence audit quality, especially audit tenure, KAP size, and time budget pressure. The research method used in this research is a quantitative research method using logistic regression analysis which is processed through SPSS version 23. The population in this study are all manufacturing companies in the transportation and logistics sector which are listed on the Indonesia Stock Exchange (IDX) during the 2019 period. , -2021. Furthermore, companies that are registered continuously and present financial audit reports regularly in the 2019-2021 period are sampled in this study. The number of samples is 12, so the total for the 2019-2021 period is 34. Based on the results of the study it shows that audit tenure, KAP size, time budget pressure do not have a significant effect on audit quality, because the longer the engagement period between the auditor and the client, it is not certain that the reduce the independence of an auditor. An auditor who works in both large and small KAPs will carry out inspections according to predetermined standards. Meanwhile, the time between the auditor and the company does not guarantee the quality of the company's audit.